Aqueous extract of Parkia biglobosa (Jacq.) R. Br. (Fabaceae) exerts antiepileptogenic, anti-amnesic, and anxiolytic-like effects in mice via mechanisms involving antioxidant and anti-inflammatory pathways - Antoine Kavaye Kandeda; Soline Menvouta; Symphorien Talom Mabou; Jonas Kouamouo; Théophile Dimo (Frontiers Media S.A., 2022)
Parkia biglobosa (Jacq.) R. Br. (Fabaceae) is a widely distributed tree, used in traditional medicine to treat amebiasis, hookworm infection, ascariasis, asthma, sterility, dental pain, headaches, cardiac disorders, and epilepsy. To date, no study on the effect of an aqueous extract of P. biglobosa on epileptogenesis and associated neuropsychiatric disorders has been undertaken. Therefore, this study aimed to investigate antiepileptogenic-, antiamnesic-, and anxiolytic-like effects of an aqueous extract of P. biglobosa using pentylenetetrazole (PTZ)-induced kindling in mice. Animals were divided into six groups of eight mice each. Thus, a PTZ group received distilled water (10 ml/kg, per os), a positive control group received sodium valproate (300 mg/kg, p.o.), and three test groups received the aqueous extract of P. biglobosa (80, 160, and 320 mg/kg, p.o.).In addition, a control group of eight mice receiving distilled water (10 ml/kg, p.o.) was formed. The treatments were administered to mice, 60 min before administration of PTZ (20 mg/kg, i.p.). These co-administrations were performed once daily, for 22 days. The number and duration of seizures (stages 1, 2, 3, and 4 of seizures) exhibited by each mouse were assessed for 30 min during the treatment period. Twenty-four hours following the last administration of the treatments and PTZ, novel object recognition and T-maze tests were performed to assess working memory impairment in mice, while the open field test was performed to assess anxiety-like behavior. After these tests, the animals were sacrificed, and the hippocampi were collected for biochemical and histological analysis. During the period of PTZ-kindling, the extract at all doses completely (p < 0.001) protected all mice against stages 3 and 4 of seizures when compared to sodium valproate, a standard antiepileptic drug. The extract also significantly (p < 0.001) attenuated working memory impairment and anxiety-like behavior. In post-mortem brain analyses, the extract significantly (p < 0.001) increased γ-aminobutyric acid (GABA) level and reduced oxidative stress and inflammation. Histological analysis showed that the aqueous extract attenuated neuronal degeneration/necrosis in the hippocampus. These results suggest that the extract is endowed with antiepileptogenic-, anti-amnesic-, and anxiolytic-like effects. These effects seem to be mediated in part by GABAergic, antioxidant, and anti-inflammatory mechanisms. These results suggest the merit of further studies to isolate the bioactive molecules responsible for these potentially therapeutically relevant effects of the extract.